Upaya Diplomasi Maritim Koersif Amerika Serikat terhadap Iran di Selat Hormuz - Ita Istiqomah; Dian Mutmainah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The Strait of Hormuz is one of the international shipping lanes for world oil and gas commodities. The unilateral withdrawal by the United States from the Joint Comprehensive Plan of Action (JCPOA) agreement in 2018 and re-imposed economic sanctions with maximum pressure. Iran responded by taking advantage of the strategic position of the Strait of Hormuz as a threat to close international shipping. The boomerang conditions for the United States to return to new behavior with Coercive Maritime Diplomacy to protect US oil trade interests and shipping security during transit in the Strait of Hormuz. The United States through the Department of Defense conducted Freedom of Navigation operations to achieve maritime diplomacy. This study uses Christian Le Miere's typology of coercive maritime diplomacy which is analyzed through three indicators: use of threats, the role of state or non-state actors, and political goals to ensure freedom of navigation. This study uses a qualitative method with data collection through literature studies from journal articles, media coverage, and official government documents, including reports from the US Department of Defense and UNCLOS.